2013
DOI: 10.2147/ijn.s30599
|View full text |Cite
|
Sign up to set email alerts
|

The physiology of cardiovascular disease and innovative liposomal platforms for therapy

Abstract: Heart disease remains the major cause of death in males and females, emphasizing the need for novel strategies to improve patient treatment and survival. A therapeutic approach, still in its infancy, is the development of site-specific drug-delivery systems. Nanoparticlebased delivery systems, such as liposomes, have evolved into robust platforms for site-specific delivery of therapeutics. In this review, the clinical impact of cardiovascular disease and the pathophysiology of different subsets of the disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 108 publications
0
18
0
Order By: Relevance
“…The in vivo cell tracking by MRI clearly showed that administered cells were preferentially located surrounding the left ventricle. These results are relevant because myocardial infarction frequently involves the left ventricle [ 34 ], so this route may initially provide an optimal cell location and retention rate in the region of interest. Interestingly, previous results from our group, using intramyocardial delivery in the same animal model under similar conditions [ 35 ], showed that cell distribution and retention is comparable to that by intrapericardial administration.…”
Section: Discussionmentioning
confidence: 99%
“…The in vivo cell tracking by MRI clearly showed that administered cells were preferentially located surrounding the left ventricle. These results are relevant because myocardial infarction frequently involves the left ventricle [ 34 ], so this route may initially provide an optimal cell location and retention rate in the region of interest. Interestingly, previous results from our group, using intramyocardial delivery in the same animal model under similar conditions [ 35 ], showed that cell distribution and retention is comparable to that by intrapericardial administration.…”
Section: Discussionmentioning
confidence: 99%
“…This study also confirms the active or passive targeting of liposomal platforms in the murine model of AMI within a week compared to the non-targeted liposomes. 157 A study combining micellar and liposomal nanoformulations for treating AMI suggests liposomes and micelles as proangiogenic and cardioprotective drug delivery systems. 158 Liposomes containing prednisone has used for the treatment of patients with atherosclerotic plaques.…”
Section: Liposomal Platformsmentioning
confidence: 99%
“…The need for targeting drugs for cardiovascular disease has become very critical [72]. Several drugs used for cardiovascular diseases have been subjected to FDA withdrawals [73].…”
Section: Organ-on-a-chip Platforms As a Potential Solutionmentioning
confidence: 99%